The Role of Oxytocin in the Dog–Owner Relationship - Marshall-Pescini, Sarah (Animals (Basel), 2019)
SIMPLE SUMMARY: A number of studies have shown that when dogs and humans interact with each other in a positive way (for example cuddling) both partners exhibit a surge in oxytocin, a hormone which has been linked to positive emotional states. It is not clear however, if this increase in oxytocin occurs between any dog and human or whether this is more specific to the dog–owner bond. In this study we measured oxytocin levels in dogs and humans before and after they interacted with their closely bonded partner (dog–owner dyads) and with a partner they were familiar with but with whom they did not have a close bond. Based on previous literature we predicted that dogs and owners would show an increase in oxytocin after a positive social interaction, and that this increase would be higher when the dog and owner were interacting with each other than when the interaction occurred with a partner that was just ‘familiar’. In fact, overall we did not find an increase in either, dogs’ or humans’ oxytocin level, although there was a lot of variability in the response. We discuss various reasons why our results are not in line with other studies. ABSTRACT: Oxytocin (OT) is involved in multiple social bonds, from attachment between parents and offspring to “friendships”. Dogs are an interesting species in which to investigate the link between the oxytocinergic system and social bonds since they establish preferential bonds with their own species but also with humans. Studies have shown that the oxytocinergic system may be involved in the regulation of such inter-specific relationships, with both dogs and their owners showing an increase in OT levels following socio-positive interactions. However, no direct comparison has been made in dogs’ OT reactivity following a social interaction with the owner vs. a familiar (but not bonded) person, so it is unclear whether relationship type mediates OT release during socio-positive interactions or whether the interaction per se is sufficient. Here we investigated OT reactivity in both dogs and owners, following a socio-positive interaction with each other or a familiar partner. Results showed neither the familiarity with the partner, nor the type of interaction affected OT reactivity (as measured in urine) in either dogs or owners. Given the recent mixed results on the role of oxytocin in dog-human interactions, we suggest there is a need for greater standardization of methodologies, an assessment of overall results taking into account ‘publication bias’ issues, and further studies investigating the role of relationship quality and interaction type on OT release.